Cortex contacts both output neurons and nitrergic interneurons in the superior colliculus: Direct and Indirect routes for multisensory integration - Fuentes-Santamaria, Veronica (2007)
The ability of cat superior colliculus (SC) neurons to integrate information from different senses is thought to depend on direct projections from regions along the anterior ectosylvian sulcus (AES). However, electrical stimulation of AES also activates SC output neurons polysynaptically. In the present study we found that nitric oxide containing (nitrergic) interneurons are a target of AES projections, forming a component of this cortico-SC circuitry. The dendritic and axonal processes of these cortico-recipient nitrergic interneurons apposed the soma and dendrites of presumptive SC output neurons. Often, an individual cortical fiber targeted both an output neuron and a neighboring nitrergic interneuron that, in turn, contacted the output neuron. Many (46%) nitrergic neurons also colocalized with γ-aminobutyric acid (GABA), suggesting that a substantial subset have the potential for inhibiting output neurons. These observations suggest that nitrergic interneurons are positioned to convey cortical influences onto SC output neurons disynaptically via nitrergic mechanisms as well as conventional neurotransmitter systems utilizing GABA and other, possibly excitatory, neurotransmitters. In addition, because NO also acts as a retrograde messenger, cortically-mediated NO release from the post-synaptic elements of nitrergic interneurons could influence presynaptic cortico-SC terminals that directly contact output neurons.